Impact of adding different levels of fenugreek and thyme leaves to the diet on some productive and physiological traits of broiler - Thamer Kadhum Mohammed Al-Abbas; Salah Mahdi Kata; Haider Qasim Baqir Al-Gharabi (Journal of Kerbala for Agricultural Sciences, 2025)
The study aimed to evaluate the effect of adding fenugreek and thyme leaf powders at different levels to the diet and their impact on the production and physiological traits of broiler chickens. A total of 210 one-day-old Ross 308 chicks were used, which were divided into seven treatments, with three replicates for each treatment and 10 birds/ replicate. The treatments were as follows: T1 (control treatment, without additives, basic diet), T2 basic diet with the addition of 2 g of fenugreek powder/kg, T3 basic diet with the addition of 4 g of fenugreek powder/kg, T4 basic diet with the addition of 2 g of thyme powder/kg, T5 basic diet with the addition of 4 gof thyme powder/kg, T6 basic diet with the addition of 1 gm of fenugreek powder and 1 g of thyme powder/kg, and T7 basic diet with the addition of 2 g of fenugreek powder and 2 g of thyme powder/kg. Treatments T2 (basic diet with the addition of 2 g of fenugreek powder/kg) and T5 (basic diet with the addition of 4 g of thyme powder/kg) significantly affected (P≤0.05) body weight, weight gain, feed intake, and feed conversion ratio. Fenugreek also altered the morphology of the intestines by increasing the height of the villi relative to the depth of the crypts.